Labor force participation of married women in China - LU, Yifei (KDI School, 2015)
Using China Health and Nutrition Survey (CHNS) data, I investigate the determinants of married women’s labor force participation in China. This study is testing hypothesis that besides the traditional economic factors, the cultural factors which have been shaped by government policies and changing economic environment have significant impact on married women’s labor force participation in China. It shows that the family of married woman, which lives near to wife’s mother, has significant positive impact on married women labor force participation. Moreover, the husband of married women, who has siblings, has positive impact on married women’s labor force participation. The fertility rate seems to have little effect on married women’s labor force participation due to the family planning program in China. Implications of the findings are discussed
Thesis(Master) --KDI School:Master of Public Policy,2015